BACKGROUND TO THE CONTEMPORARY KENYAN DEMOCRACY: FROM COLONIAL TO 1991 - Juma, Wamalwa; Cletus, Chukwu N.; Mary, Wahome N. (IJRDO - Journal of Social Science and Humanities Research, 2018)
Kenya has been described as one the growing democracies in Africa.  Beginning the 1992 with the establishment of Multi party politics, the country has realized  some notable democratic developments including regular and competitive elections, working institutions, rule of law, working civil society, respect of human rights among others.  These present achievement, however, are anchored on experiences which provided the impetus and acted as a fertile ground for the establishment of democracy in the country.  This paper examines experiences in Kenya from the colonial period up to 1991 when the country become a multi party state, and subsequently a democracy.  The paper examines the four regimes, pre-colonial, the colonial regime, Kenyatta regime and the first phase of Moi regime.